CASK regulates CaMKII autophosphorylation in neuronal growth, calcium signaling, and learning - Gillespie, John M.; Hodge, James J. (Frontiers in Molecular Neuroscience, 2013)
Calcium (Ca2+)/calmodulin (CaM)-dependent kinase II (CaMKII) activity plays a fundamental role in learning and memory. A key feature of CaMKII in memory formation is its ability to be regulated by autophosphorylation, which switches its activity on and off during synaptic plasticity. The synaptic scaffolding protein CASK (calcium (Ca2+)/calmodulin (CaM) associated serine kinase) is also important for learning and memory, as mutations in CASK result in intellectual disability and neurological defects in humans. We show that in Drosophila larvae, CASK interacts with CaMKII to control neuronal growth and calcium signalling. Furthermore, deletion of the CaMK-like and L27 domains of CASK (CASK β null) or expression of overactive CaMKII (T287D) produced similar effects on synaptic growth and Ca2+ signalling. CASK overexpression rescues the effects of CaMKII overactivity, consistent with the notion that CASK and CaMKII act in a common pathway that controls these neuronal processes. The reduction in Ca2+ signalling observed in the CASK β null mutant caused a decrease in vesicle trafficking at synapses. In addition, the decrease in Ca2+ signalling in CASK mutants was associated with an increase in Ether-à-go-go (EAG) potassium (K+) channel localisation to synapses. Reducing EAG restored the decrease in Ca2+ signalling observed in CASK mutants to the level of wildtype, suggesting that CASK regulates Ca2+ signalling via EAG. CASK knockdown reduced both appetitive associative learning and odour evoked Ca2+ responses in Drosophila mushroom bodies, which are the learning centres of Drosophila. Expression of human CASK in Drosophila rescued the effect of CASK deletion on the activity state of CaMKII, suggesting that human CASK may also regulate CaMKII autophosphorylation.